Lawyer-client relationship in divorce proceedings: development and validation of a new instrument - Martínez-Pampliega, Ana; Cormenzana, Susana; García-Garnica, Ma Carmen; Pellón-Elexpuru, Inés; Merino, Laura (Frontiers in Psychology, 2024)
This study is based on the paradigm of collaborative law and the current absence of instruments that evaluate the lawyer-client relationship as a function of the needs of the family system. The objective was to construct and validate an instrument, conceptualizing the lawyer-client relationship as a helping relationship. Method: Two groups of experts and 239 parents (58% mothers and 42% fathers), users of Family Visitation Centers, participated in the study. The content, construct, and criterion validity of the instrument, as well as its invariance for both parents, were analyzed. Results: The resulting 12-item instrument has been shown to have a two-dimensional structure, invariant for both parents, with high psychometric solidity. Discussion: The LCR scale seems to be a valuable and effective measure for use in a legal context, with important correlations with the parents' psychological well-being, leading to a promising and relevant instrument for the holistic approach to the divorce process.